Abnormal haemoglobins, Hb Takamatsu and Hb G-Szuhu, detected during the analysis of glycated haemoglobin (HbA1C) by high performance liquid chromatography. Issue 11 (1st November 2000) - Moriwaki, Y; Yamamoto, T; Shibutani, Y; Harano, T; Takahashi, S; Hada, T
Abstract : Background —During medical checkups of two unrelated female outpatients during their annual health examination and one male inpatient suffering from cardiac failure the glycated haemoglobin (HbA1C ) concentrations measured by high performance liquid chromatography (HPLC) were low, in spite of normal fasting plasma glucose concentrations. However, HbA1C concentrations measured by latex immunoagglutination and fructosamine concentrations were within the normal range. Method —Investigations were performed to elucidate the reasons for these discrepancies. Results —Abnormal haemoglobins, Hb Takamatsu and Hb G-Szuhu, were found. The HPLC chromatogram showed an additional peak near HbA1a+b, which resulted in falsely low HbA1C concentrations. Isoelectric focusing analysis of the patients' haemoglobin disclosed abnormal haemoglobins, which migrated faster than normal HbA1 in the two female patients and slower in the male patient. The cDNA sequence and amino acid analyses of the haemoglobin α-chains and β-chains indicated the presence of the haemoglobin variant β 120 Lys→Gln in the two female patients and β 80 Asn→Lys in the male patient; that is, Hb Takamatsu and Hb G-Szuhu. Conclusions —These cases show how these silent haemoglobin variants can result in falsely low HbA1C concentration readings when using HPLC.